2004
DOI: 10.1046/j.1439-037x.2003.00082.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Use Efficiency of Spring Wheat Genotypes under Field and Lysimeter Conditions

Abstract: Lysimeters and neighbouring fields were used from 1998 to 2000 to assess parameters of N use efficiency of three Swiss spring wheat (Triticum aestivum L.) genotypes. An old (Albis), a new (Toronit) and an experimental genotype (L94491) were compared with no and ample (250 kg N ha−1) N fertilizer supply. N fertilization increased biomass, grain yield and grain N concentration of all genotypes in all years and in both testing systems (field, lysimeters) but only a few genotype × N interactions were observed. Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 33 publications
3
16
0
Order By: Relevance
“…In another study, Thanapornpoonpong (2004) also demonstrated the positive effect of nitrogen fertilization on seed nitrogen content of quinoa crop. Similarly, increase of grain nitrogen accumulation and concentation was caused in other crops (wheat, soybean) by nitrogen fertilization (Hayati et al, 1996;Noulas et al, 2004). Moreover, Delogu et al (1998) demonstrated that after application of 80 kg N ha -1 in barley, the nitrogen content in grain was enhanced by about 18% compared to the control.…”
Section: Discussionmentioning
confidence: 90%
“…In another study, Thanapornpoonpong (2004) also demonstrated the positive effect of nitrogen fertilization on seed nitrogen content of quinoa crop. Similarly, increase of grain nitrogen accumulation and concentation was caused in other crops (wheat, soybean) by nitrogen fertilization (Hayati et al, 1996;Noulas et al, 2004). Moreover, Delogu et al (1998) demonstrated that after application of 80 kg N ha -1 in barley, the nitrogen content in grain was enhanced by about 18% compared to the control.…”
Section: Discussionmentioning
confidence: 90%
“…Globally, wheat accounts for about 17% of total fertilizer use and 19% of the total nitrogen fertilizer consumption. A number of authors show that about 45-85% of the applied nitrogen fertilizer is recovered by the plant (Addiscot, 1996;King et al, 2001;Ma et al, 2009;Noulas et al, 2004). On average, about 16% of the applied nitrogen is presumed to be lost either by denitrification or leaching (Addiscot, 1996).…”
Section: Datamentioning
confidence: 99%
“…As NUE range and NHI range were only rough estimates, they were not necessarily included in statistical analyses. Benchmarking with documented cereal NHI values, showed our NHI range estimates to be close to or even exceeding 80% (Spiertz and de Vos 1983, Feil 1997, Noulas et al 2004), though NHI is strongly affected by e.g. weather conditions (Feil, 1997).…”
Section: Methodsmentioning
confidence: 52%
“…In northern Europe this occurs, for example, when N is not taken up adequately at pre-heading because of typical early summer drought (Peltonen-Sainio et al 2010), manure is used or elevated late summer temperatures stimulate excess N mobilization from soil (Rajala et al 2007). Typically N uptake values for fertilized wheat (Triticum aestivum L.) and barley (Hordeum vulgare L.) range from 20% to 100% of fertiliser applied in temperate regions (Gauer et al 1992, Le Gouis et al 2000, Sinebo et al 2003, Noulas et al 2004). This indicates considerable induced variability in N uptake according to growing conditions and challenges sustainable and economic fertilizer use.…”
Section: Introductionmentioning
confidence: 99%